Gasoline compression ignition (GCI) combustion in a light-duty engine using double injection strategy. (25th March 2023) - Agarwal, Avinash Kumar; Solanki, Vishnu Singh; Krishnamoorthi, M.
Highlights: Split injection improved fuel economy and emissions simultaneously. Retarded main injection showed stable combustion and higher efficiency. Pilot injection and load strongly influenced HRR and combustion phasing. CO and HC emisions increased with charge homogeneity but decreased with engine load. GCI engine emitted higher nucleation mode particles but lower PM mass. Abstract: Controlling the oxides of nitrogen (NOx) and particulate matter (PM) emissions is one of the vital goals of compression ignition (CI) engines. Implementing stringent emissions regulations has motivated researchers to adopt various strategies for controlling emissions. Gasoline compression ignition (GCI) has emerged as a prime technology to control emissions and increase engine efficiency, while using low-octane gasoline as fuel in CI engines. Preheated air, hot exhaust gas recirculation (EGR), and negative valve overlap, are required to manage the combustion instabilities in the GCI engines. However these techniques have not been used in this study in order to reduce system complexity. Low octane test fuel was prepared (G80) by blending 80 % v/v gasoline and 20 % v/v diesel. This study involved experiments to evaluate the effects of main injection timing, split injection quantities (10–30 %), and engine load (brake mean effective pressure (BMEP): 3–5 bar) on a two-cylinder GCI engine's performance, combustion, cyclic variability, emissions, and particulates. Conventional diesel combustion (CDC) mode experiments were performed using diesel. The results indicated a 5 % higher brake thermal efficiency (BTE) and comparable exhaust gas temperature (EGT) for the GCI mode compared to the baseline CDC mode. GCI combustion with low split ratio showed higher in-cylinder pressure than CDC mode. Baseline CDC mode showed < 3 % coefficient of variation of indicated mean effective pressure and peak pressure, whereas these parameters varied from 1 % to 9 % in the GCI mode. GCI mode engine exhibited ∼ 60 and 50 % lower NOx and PM emissions than baseline diesel mode engine. The double injection strategy improved GCI engine's performance and emission characteristics.